Clinical Significance of Preoperative Pyrazinamide-Containing Therapy in Tuberculous Constrictive Pericarditis - Fang L; Yu W; Yu G; Chen G; Ye B (Infection and Drug Resistance, 2024)
Likui Fang, Wenfeng Yu, Guocan Yu, Gang Chen, Bo Ye Department of Thoracic Surgery, Hangzhou Red Cross Hospital, Hangzhou, 310003, People’s Republic of ChinaCorrespondence: Likui Fang, Department of Thoracic Surgery, Hangzhou Red Cross Hospital, Hangzhou, 310003, People’s Republic of China, Email 21618100@zju.edu.cnBackground: Tuberculous constrictive pericarditis (TCP) is recommended to be treated with anti-tuberculosis (TB) therapy before pericardiectomy. Whether different preoperative anti-TB regimens may lead to different outcomes is unclear.Methods: We retrospectively collected patients diagnosed as TCP and received pericardiectomy from April 2016 to June 2023. The study patients were assigned into the active TCP (A-TCP) group and the inactive TCP (IA-TCP) group according to the results of Mycobacterium tuberculosis (MTB) culture and MTB RNA assay. Baseline characteristics including anti-TB regimens and surgical outcomes were compared between the two groups. Logistic regression analysis and subgroup analysis were conducted to identify the protective factors of A-TCP.Results: Of the 102 study patients, 24 was in the A-TCP group and 78 was in the IA-TCP group. The rate of preoperative anti-TB regimen containing pyrazinamide was 37.5% in the A-TCP group, as compared with 74.4% in the IA-TCP group (P = 0.001). Multivariate analysis showed that preoperative use of pyrazinamide was the protective factor of A-TCP (OR 0.194, 95% CI 0.053– 0.703, P = 0.013). Subgroup analysis based on age also showed consistent findings. In the analyses of surgical outcomes, A-TCP was the independent risk factor of postoperative cardiac complications (OR 4.231, 95% CI 1.317– 13.593, P = 0.015) and associated with longer hospital stay (P = 0.004) and higher hospitalization cost (P = 0.001).Conclusion: A strategy involving anti-TB regimen containing pyrazinamide before pericardiectomy was superior to that without pyrazinamide in the patients with TCP. The strategy was associated with lower risk of A-TCP and might lead to better postoperative recovery and cost-effectiveness.Keywords: tuberculous constrictive pericarditis, pericardiectomy, pyrazinamide, outcomes